Phagocytosis by macrophages depends on histamine H2 receptor signaling and scavenger receptor 1. Issue 10 (1st August 2019) - Fultz, Robert; Engevik, Melinda A.; Shi, Zhongcheng; Hall, Anne; Herrmann, Beatrice; Ganesh, Bhanu P.; Major, Angela; Haag, Anthony; Mori‐Akiyama, Yuko; Versalovic, James
Abstract: The histamine H2 receptor (H2R) is a G protein‐coupled receptor that mediates cyclic AMP production, protein kinase A activation, and MAP kinase signaling. In order to explore the multifaceted effects of histamine signaling on immune cells, phagocytosis was evaluated using primary mouse‐derived macrophages. Phagocytosis is initiated by signaling via surface‐bound scavenger receptors and can be regulated by autophagy. Absence of H2R signaling resulted in diminished phagocytosis of live bacteria and synthetic microspheres by primary macrophages from histamine H2 receptor gene ( Hrh2 )‐deficient mice. Flow cytometry and immunofluorescence microscopy were used to quantify phagocytosis of phylogenetically diverse bacteria as well as microspheres of defined chemical composition. Autophagy and scavenger receptor gene expression were quantified in macrophages after exposure to Escherichia coli . Expression of the autophagy genes, Becn1 and Atg12, was increased in Hrh2 −/− macrophages, indicating upregulation of autophagy pathways. Expression of the Macrophage Scavenger Receptor 1 gene ( Msr1 ) was diminished in Hrh2 ‐deficient macrophages, supporting the possible importance of histamine signaling in scavenger receptor abundance and macrophage function. Flow cytometry confirmed diminished MSR1 surface abundance in Hrh2 −/− macrophages. These data suggest that H2R signaling is required for effective phagocytosis by regulating the process of autophagy and scavenger receptor MSR1 abundance in macrophages. Abstract : We demonstrate that histamine 2 receptor is required for phagocytosis of bacteria and microspheres by mouse macrophages. Expression of key autophagy pathway genes is increased, and Macrophage Scavenger Receptor 1 is decreased in abundance in histamine 2 receptor‐deficient macrophages.